2021
DOI: 10.21203/rs.3.rs-121821/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM reveals the architecture of placental malaria VAR2CSA and provides molecular insight into chondroitin sulfate binding

Abstract: Malaria during pregnancy remains a major health problem in Plasmodium falciparum endemic areas. Parasite-infected red blood cells sequester in the placenta through interaction between parasite-expressed protein VAR2CSA and the glycosaminoglycan chondroitin sulfate A (CS) abundantly present in the intervillous space. Placental malaria can have severe consequences for both mother and child by causing maternal anemia, low birth weight and stillbirth. Several VAR2CSA-based vaccines have been developed and clinical… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…They elicited antibody against the homologous VAR2CSA variant that blocked CSA binding but showed little or no recognition of other variants. Studies have shown how the VAR2CSA protein is folded to create one, or possibly two, conserved binding regions for CSA [27,28 ▪ ,29 ▪ ]. These binding regions are highly conserved, while adjacent polymorphic and flexible regions may be the main targets for antibodies.…”
Section: Vaccines For Malaria In Pregnancymentioning
confidence: 99%
“…They elicited antibody against the homologous VAR2CSA variant that blocked CSA binding but showed little or no recognition of other variants. Studies have shown how the VAR2CSA protein is folded to create one, or possibly two, conserved binding regions for CSA [27,28 ▪ ,29 ▪ ]. These binding regions are highly conserved, while adjacent polymorphic and flexible regions may be the main targets for antibodies.…”
Section: Vaccines For Malaria In Pregnancymentioning
confidence: 99%
“…In human melanoma cell lines and melanoma tissue, decline in ARSB increased PD-L1 (programmed death ligand-1) expression [76]. Silencing ARSB by siRNA also increased PD-L1 expression in human prostatic and hepatic cell lines.…”
Section: Increased Programmed Death-ligand 1 (Pd-l1)mentioning
confidence: 99%
“…In experiments in prostate stromal and epithelial cells, when ARSB was silenced, binding of galectin-3 with C4S declined, nuclear galectin-3 increased and facilitated the binding of transcription factor AP-1 to the versican promoter [26]. Increased expression of CSPG4 (chondroitin sulfate proteoglycan 4) [32] and of PD-L1 [76] in human melanoma cells are also dependent on galectin-3. Expression of HIF-1α in human bronchial epithelial cells and in the colonic epithelial cell line NCM460 increased when ARSB was silenced and declined when ARSB was overexpressed [34].…”
Section: Activation Of Galectin-3 (Lgals3)mentioning
confidence: 99%
“…After treatment with chymotrypsin, LC-MS/MS was used to compare the oxidation differences of each peptide. Finally, it was found that the peptide with the largest redox is peptide 543-558, which proves that the surface of the DBL2 and Hb1 groove acts as a CS binding region (Wang K. et al, 2020). The irradiation conditions of HRF must be carefully controlled to avoid secondary modification of the protein.…”
Section: Msmentioning
confidence: 99%
“…Hydroxyl radical footprinting (HRF) uses hydroxyl radicals to rapidly oxidize amino acid side chains (Maleknia and Downard, 2014), which is a covalent labeling method for characterizing GAGprotein complexes. Wang K. et al (2020) used hydroxyl radical HRF to characterize the binding sites between CS and the protein VAR2CSA expressed by the parasite. Hydroxyl radicals were used to rapidly oxidize the recombinantly expressed DBL1-ID2 protein with and without CS.…”
Section: Msmentioning
confidence: 99%